Transesophageal echocardiographic diagnosis of a WATCHMAN left atrial appendage closure device thrombus 10 years following implantation. Issue 1 (16th November 2016) - Shamim, Shariq; Magalski, Anthony; Chhatriwalla, Adnan K.; Allen, Keith B.; Huber, Kenneth C.; Main, Michael L.
Abstract : Left atrial appendage closure with the WATCHMAN device is an alternative to chronic oral anticoagulation for thromboembolic prophylaxis in atrial fibrillation patients. Left atrial device‐related thrombus (DRT) has been described in the first year after implant with an incidence of 6%. A 79‐year‐old man underwent WATCHMAN device placement in 2006. Routine protocol specified follow‐up transesophageal echocardiograms (TEE) at 6 weeks, 6 months, and 1 year following implant showed no evidence for DRT or peri‐device flow. A decade after device implant, the patient presented with severe symptomatic aortic stenosis and underwent repeat TEE, which revealed a 21 mm × 18 mm DRT on the LA aspect of the WATCHMAN device. He was prescribed apixaban 5 mg po BID. A TEE performed 111 days later demonstrated marked diminution in the DRT (9 mm in diameter). This case demonstrates that WATCHMAN DRT may occur late following implantation.